PROYECTO DE ORDENANZA PARA LA ASIGNACIÓN DE NOMBRE A LAS CALLES RECIÉN ABIERTAS EN EL CENTRO PARROQUIAL DE CHUQUIRIBAMBA - Buri Puchaicela, Nancy Elizabeth (2016)
Chuquiribamba is one of the oldest parishes in Loja Canton which is located north-west of the city of Loja, joined by a third order road at a distance of 49.10 Km, adorned by countless hills that are the guardians of the parish and their green crops. In this parish they conducted a study on the population to the declaration as Cultural Patrimony of Ecuador about the history of the houses, streets and customs that keep them favored for this designation, noting the potential of community tourism that gives the area, mechanism of drafting the horchata, strawberry plantations, the famous traditional mock skirmishes or run horses and because Chuquiribamba is the birthplace of famous men and women who have excelled in the field of music, art, entrepreneurship and letters . To the draft Ordinance naming newly opened streets of the parish Chuquiribamba header was necessary to collect as much bibliographic information as the result of interviews with members of organizations, leaders and relatives of famous people and sights of Chuquiribamba. Then he proceeded to make a list of the various characters and proposed tourist sites and with this information a survey was applied to citizens of the parish center of Chuquiribamba was formulated. With the results of the survey could determine what the appropriate names of famous people and tourist to assign to each of naming the streets without meeting the objectives proposed by this research places. Finally conclusions and recommendations above Ordinance is done stressing that this project is a sign of cultural rescue worthy of this prestigious parish of being declared Cultural Heritage of Ecuador.